Intergenerational conflicts of interest and prosocial behavior during the COVID-19 pandemic. (March 2021) - Jin, Shuxian; Balliet, Daniel; Romano, Angelo; Spadaro, Giuliana; van Lissa, Caspar J.; Agostini, Maximilian; Bélanger, Jocelyn J.; Gützkow, Ben; Kreienkamp, Jannis; Leander, N. Pontus; ,
Abstract: The COVID-19 pandemic presents threats, such as severe disease and economic hardship, to people of different ages. These threats can also be experienced asymmetrically across age groups, which could lead to generational differences in behavioral responses to reduce the spread of the disease. We report a survey conducted across 56 societies ( N = 58, 641), and tested pre-registered hypotheses about how age relates to (a) perceived personal costs during the pandemic, (b) prosocial COVID-19 responses (e.g., social distancing), and (c) support for behavioral regulations (e.g., mandatory quarantine, vaccination). We further tested whether the relation between age and prosocial COVID-19 responses can be explained by perceived personal costs during the pandemic. Overall, we found that older people perceived more costs of contracting the virus, but less costs in daily life due to the pandemic. However, age displayed no clear, robust associations with prosocial COVID-19 responses and support for behavioral regulations. We discuss the implications of this work for understanding the potential intergenerational conflicts of interest that could occur during the COVID-19 pandemic.